(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
This essay aims to show in a general way: what is the perception that anthropology students of the Universidad del Magdalena, Santa Marta Colombia, have about the function of reading classical texts. For this purpose, this text starts from the question: What is the function in the implementation of the reading of classical writings, which under analysis and guidelines marked by the Eurocentric academy, inquire about the socio-cultural dynamics? Analyzing different postulates and the changes in the anthropological work, this paper develops different arguments that conclude in the proposition of the implementation of parallelism in the reading of classical texts with the current ones, since this allows a better intellectual appropriation and with it the conformation of a critical thinking outside the hegemonic classical schemes.